Metabolic Control of Dendritic Cell Functions: Digesting Information - Wculek, Stefanie K.; Khouili, Sofía C.; Priego, Elena; Heras-Murillo, Ignacio; Sancho, David (Frontiers in Immunology, 2019)
Dendritic cells (DCs) control innate and adaptive immunity by patrolling tissues to gather antigens and danger signals derived from microbes and tissue. Subsequently, DCs integrate those environmental cues, orchestrate immunity or tolerance and regulate tissue homeostasis. Recent advances in the field of immunometabolism highlight the notion that immune cells markedly alter cellular metabolic pathways during differentiation or upon activation, which has important implications on their functionality. Previous studies showed that active oxidative phosphorylation in mitochondria is associated with immature or tolerogenic DCs, while increased glycolysis upon pathogen sensing can promote immunogenic DC functions. However, new results in the last years suggest that regulation of DC metabolism in steady state, after immunogenic activation and during tolerance in different pathophysiological settings may be more complex. Moreover, ontogenically distinct DC subsets show different functional specializations to control T cell responses. It is thus relevant how metabolism influences DC differentiation and plasticity, and what potential metabolic differences exist among DC subsets. Better understanding of the emerging connection between metabolic adaptions and functional DC specification will likely allow the development of therapeutic strategies to manipulate immune responses.